ADAM17‐triggered TNF signalling protects the ageing Drosophila retina from lipid droplet‐mediated degeneration. (26th July 2020) - Muliyil, Sonia; Levet, Clémence; Düsterhöft, Stefan; Dulloo, Iqbal; Cowley, Sally A; Freeman, Matthew
Abstract: Animals have evolved multiple mechanisms to protect themselves from the cumulative effects of age‐related cellular damage. Here, we reveal an unexpected link between the TNF (tumour necrosis factor) inflammatory pathway, triggered by the metalloprotease ADAM17/TACE, and a lipid droplet (LD)‐mediated mechanism of protecting retinal cells from age‐related degeneration. Loss of ADAM17, TNF and the TNF receptor Grindelwald in pigmented glial cells of the Drosophila retina leads to age‐related degeneration of both glia and neurons, preceded by an abnormal accumulation of glial LDs. We show that the glial LDs initially buffer the cells against damage caused by glial and neuronally generated reactive oxygen species (ROS), but that in later life the LDs dissipate, leading to the release of toxic peroxidated lipids. Finally, we demonstrate the existence of a conserved pathway in human iPS‐derived microglia‐like cells, which are central players in neurodegeneration. Overall, we have discovered a pathway mediated by TNF signalling acting not as a trigger of inflammation, but as a cytoprotective factor in the retina. Synopsis: The metalloprotease ADAM17 triggers a signalling mechanism that controls lipid droplet formation and cell survival in the Drosophila retina. Absence of Drosophila ADAM17 in retinal glial cells results in abnormal lipid droplet accumulation, elevated peroxidated lipids, and subsequent age‐associated degeneration. Loss of TNF, encoded by the eiger gene, or the TNF receptor Grindelwald, causes the same retinal degeneration phenotype. Retinal degeneration in ADAM17 mutants can be rescued by overexpressing lipase in glial but not neuronal cells. Reactive oxygen species generated by neuronal activity contribute to the lipid droplet‐mediated retinal degeneration in ADAM17 mutants. In human iPSC microglia‐like cells, loss of ADAM17 also results in elevated peroxidated lipids and lipid droplet formation. Abstract : Modulation of ROS‐buffering glial cell lipid droplets constitutes an unexpected cytoprotective role of inflammatory metalloprotease/tumour necrosis factor pathways, which appears conserved in microglia‐like human cells.